Enzymatic protection and biocompatibility screening of enzyme-loaded polymeric nanoparticles for neurotherapeutic applications. (October 2020) - Liao, Rick; Pon, Jessica; Chungyoun, Michael; Nance, Elizabeth
Abstract: Polymeric nanoparticles provide a non-invasive strategy for enhancing the delivery of labile hydrophilic enzymatic cargo for neurological disease applications. One of the most common polymeric materials, poly(lactic-co-glycolic acid) (PLGA) copolymerized with poly(ethylene glycol) (PEG) is widely studied due to its biocompatible and biodegradable nature. Although PLGA-PEG nanoparticles are generally known to be non-toxic and protect enzymatic cargo from degradative proteases, different formulation parameters including surfactant, organic solvent, sonication times, and formulation method can all impact the final nanoparticle characteristics. We show that 30s sonication double emulsion (DE)-formulated nanoparticles achieved the highest enzymatic activity and provided the greatest enzymatic activity protection in degradative conditions, while nanoprecipitation (NPPT)-formulated nanoparticles exhibited no protection compared to free catalase. However, the same DE nanoparticles also caused significant toxicity on excitotoxicity-induced brain tissue slices, but not on healthy or neuroinflammation-induced tissue. We narrowed the culprit of toxicity to specifically sonication of PLGA-PEG polymer with dichloromethane (DCM) as the organic solvent, independent of surfactant type. We also discovered that toxicity was oxidative stress-dependent, but that increased toxicity was not enacted through increasing oxidative stress. Furthermore, no PEG degradation or aldehyde, alcohol, or carboxylic acid functional groups were detected after sonication. We identified that inclusion of free PEG along with PLGA-PEG polymer during the emulsification phases or replacing DCM with trichloromethane (chloroform) produced biocompatible polymeric nanoparticle formulations that still provided enzymatic protection. This work encourages thorough screening of nanoparticle toxicity and cargo-protective capabilities for the development of enzyme-loaded polymeric nanoparticles for the treatment of disease.